Systematic Literature: The Role of Transformational Leadership in Increasing Employee Productivity and Retention in the Freelance Day Worker System in the Manufacturing Industry - Frisdayanti, Devina Octa; Choirunnisa, Zuyyinna (Eduvest - Journal of Universal Studies, 2025)
This study examines the role of transformational leadership in enhancing productivity and retention among freelance manufacturing workers, addressing the challenges of job instability and low engagement in gig-based employment systems. The research problem focuses on how transformational leadership can mitigate these issues by fostering intrinsic motivation, work engagement, and organizational commitment. The objectives include analyzing the impact of transformational leadership on worker performance, identifying mediating factors like work-life balance, and providing actionable strategies for leaders in the manufacturing sector. A systematic literature review was conducted using the PRISMA method, analyzing six peer-reviewed articles from databases such as Scopus and Web of Science (2019–2023). Key findings reveal that transformational leadership significantly boosts productivity by inspiring workers, providing clear vision, and offering individualized support. Mediating factors like intrinsic motivation and work-life balance were critical in improving retention, while organizational commitment further strengthened performance outcomes. The study highlights the importance of adaptive leadership styles, digital tools for engagement, and inclusive recognition programs to sustain freelance worker loyalty. Practical implications include recommendations for leadership training programs and the integration of technology to enhance communication and feedback. Theoretically, the study contributes to understanding how transformational leadership can be tailored to non-traditional work arrangements. By addressing the unique needs of freelance workers, this research offers a framework for manufacturing firms to improve productivity and reduce turnover in an evolving labor market.